Mindfulness Relationship With Student Life Satisfaction In Learning During The Covid-19 Pandemic - Mirandha, Yolla; Firman, Firman (Current Issues in Counseling, 2021)
Today in the era of the Covid-19 pandemic, this study aims to: (1) describe the mindfulness of students in learning during the Covid-19 pandemic, (2) describe student life satisfaction in learning during the Covid-19 pandemic, and (3) test Mindfulness relationship with student life satisfaction in learning during the Covid-19 pandemic. The research approach used a quantitative approach with a descriptive correlational type. The population in this study were students of SMA Negeri 2 Sungai Limau with a proportional random sampling technique. Data collection was carried out through mindfulness and student life satisfaction questionnaires in learning. Furthermore, the data were analyzed using descriptive statistics with percentage techniques, and to test for normality, linear test and the relationship between the two variables used statistical analysis using the Pearson product moment technique with the help of SPSS version 20.0 for windows. Based on the results of the study, it was found: (1) students' mindfulness was in the high category with an average percentage of 43%, (2) the life satisfaction of students was in the medium category with an average percentage of 70.3% and (3) there was a relationship between mindfulness and Student life satisfaction in learning during the Covid-19 pandemic was 0.632 with a significant level of 99%. The implication of guidance and counseling services is that guidance and counseling teachers provide services to students related to mindfulness problems and student life satisfaction in learning during the Covid-19 pandemic.